2020
DOI: 10.3390/agriculture10100479
|View full text |Cite
|
Sign up to set email alerts
|

Packaging in a High O2 or Air Atmospheres and in Microperforated Films Effects on Quality of Button Mushrooms Stored at Room Temperature

Abstract: Cold conditions are obligatory for mushrooms storage. However, in most cases, the cold chain is interrupted at various stages. Thus, is of great importance to propose a packaging system capable of inhibiting the detrimental effect of high temperature on mushrooms’ quality. The study evaluates the effect of high oxygen atmosphere (80% O2) in conjunction with films of different levels of microperforations (polysulfon (PSF) films, low: PSF_1000, PSF_2000; medium: PSF_3500; and high: PSF_7000) on antioxidant capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 51 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…The low water loss in the case of PVC is caused probably due to its low perforation degree. The PVC is characterized by low water permeability [29,30]. We observed that, in the case of active packaging with aҫai extract + zeolite and zeolite (0.5% w/v and 1% w/v) packed with perforated foil, there was no statistical differences in comparison to PVC foil on the last day of storage (day 28).…”
Section: Weight Loss and Texturementioning
confidence: 79%
“…The low water loss in the case of PVC is caused probably due to its low perforation degree. The PVC is characterized by low water permeability [29,30]. We observed that, in the case of active packaging with aҫai extract + zeolite and zeolite (0.5% w/v and 1% w/v) packed with perforated foil, there was no statistical differences in comparison to PVC foil on the last day of storage (day 28).…”
Section: Weight Loss and Texturementioning
confidence: 79%
“…Following these wounds, the mushroom respiration rate increases, and plant tissues age (Fonseca et al, 2002). Because the respiration of harvested mushrooms is closely related to their quality, this phenomenon has been quantified (Jacxsens et al, 2001;Pogorzelska-Nowicka et al, 2020). In this study, although there was no significant change in proportion of the mycelium, the CO2 emission rate of mycelium changed significantly (Table 2).…”
Section: Discussionmentioning
confidence: 71%
“…Utilizing high oxygen levels and micro-perforated films, color and volatile components were preserved, maintaining the color and consumer acceptance. Additionally, it stops water condensation and the creation of unwelcome volatile chemicals inside mushroom packaging, but it has been found to lower pH levels ( Pogorzelska-Nowicka et al., 2020 ). A recommended environment for storing mushrooms is 2.5–5% CO 2 and 5–10% O 2 , in addition to polythene bags of thickness 100 gauges with a 0.5 percent venting area for packing mushrooms in refrigeration situations ( Wakchaure, 2011 ).…”
Section: Latest Technology For Preservation Of Mushroomsmentioning
confidence: 99%